Terahertz spectroscopy of conducting polypyrrole (p-TS) - Rempillo, Ofelia T. (Animo Repository, 2005)
Conducting polypyrrole doped with para-tuluoene sulphonate (PPy p-TS) were synthesized galvanostatically using a three electrode cell at synthesis parameters of 0.1 M PPy, 0.1 M p-TS, 20 C/cm2 charge density, 3-5 mA/cm2 current density. Resistivity versus temperature measurements were obtained using Van der pauw technique. Optical Characterization was done using Terahertz spectroscopy. The free standing polypyrrole films obtained had thickness ranging from 12-69 µm and room temperature conductivities ranging from 18.04 88.77 S/cm. Images of the film surface showed globular and fibrillar structure. Resistivity versus temperature plots showed decreasing resisitivity with increasing temperature characteristic of a semiconductor. Results were fit with Motts three dimensional variable range hopping. Motts hopping parameters obtained, T0 = 1.62-12.1 x 104 K, NF = 5.87 44.0 x 1021 ev-1cm-3, R = 6.59 10.9 Å at 300 K and W = 19.0 31.4 meV at 300 K were of the same order of magnitude as those obtained in previous studies. Terahertz transmission measurements at room temperature showed increasing absorption coefficient with increasing conductivity indicating free charge carrier absorption as the dominant absorption mechanism. Temperature dependent measurements exhibited a general trend of decreasing transmitted power and increasing absorption with increasing temperature. Absorption peaks were observed at 0.2 THz and 0.3 THz (6.7 cm-1 to 10 cm-1) for samples A3, A5 and A6 that have not been identified in previous studies.